ANALYSIS OF IMPORTANCE AND PERFORMANCE STUDENT SATISFACTION, STUDENT LOYALTY, AND COMPETITIVE ADVANTAGE PRIVATE UNIVERSITIES - Julius Nursyamsi; Didin Mukodim; Peni Sawitri (Asosiasi Dosen Muda Indonesia, 2022)
This study examines and evaluates the constructs of service quality, website quality, institutional image, marketing mix, student satisfaction, student loyalty and competitive advantage based on structural equation modeling. This research model illustrates that each construct has a performance value and importance to competitive advantage. The test of this model uses a sample of 932 active student respondents at private universities with a non-probability sampling method with a purposive sampling technique. Data analysis using structural equation modeling and importance-performance map analysis, test analysis tool with SmartPLS. Based on the results of the analysis, it was found that the quality of the website has a low importance and performance value on competitive advantage compared to other variables.